2023
DOI: 10.3389/fphys.2023.1115250
|View full text |Cite
|
Sign up to set email alerts
|

The role of bile acid in intestinal metaplasia

Abstract: A precancerous lesion of gastric cancer (GC), intestinal metaplasia (IM) is a pathological transformation of non-intestinal epithelium into an intestinal-like mucosa. It greatly raises the risk of developing the intestinal type of GC, which is frequently observed in the stomach and esophagus. It is understood that esophageal adenocarcinoma’s precursor lesion, chronic gastroesophageal reflux disease (GERD), is what causes Barrett’s esophagus (BE), an acquired condition. Recently, Bile acids (BAs), which are one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…The EGFR/PI3K/AKT pathway is abnormally activated in the PLGC rat model (including CAG, GIM, and dysplasia), and inhibiting this pathway can effectively improve PLGC [4]. Meanwhile, a key report suggested that BA may promote GIM through the EGFR signaling pathway [9]. Here, our experimental results indicate that DCA can abnormally activate the EGFR/PI3K/AKT/mTOR pathway, promote protein expression of CDX2, MUC2, Ki-67, Cyclin-D1, and induce GIM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EGFR/PI3K/AKT pathway is abnormally activated in the PLGC rat model (including CAG, GIM, and dysplasia), and inhibiting this pathway can effectively improve PLGC [4]. Meanwhile, a key report suggested that BA may promote GIM through the EGFR signaling pathway [9]. Here, our experimental results indicate that DCA can abnormally activate the EGFR/PI3K/AKT/mTOR pathway, promote protein expression of CDX2, MUC2, Ki-67, Cyclin-D1, and induce GIM.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation stimulates the gastric mucosa for a long time, which can induce abnormal cell proliferation, AGING promote morphological and functional variations of cells, and then induce GIM or promote the development of GIM toward GC [6][7][8]. Bile reflux is an important factor that triggers or accelerates chronic inflammation [9]. Deoxycholic acid (DCA), as a hydrophobic secondary bile acid (BA), is the main component of bile reflux [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, little research has focused on the effects of BAs alone, independent of acidity, on the development of BO and OAC. It is thought that BAs upregulate the expression of metaplasia-promoting genes leading to the columnar-cell phenotype characteristic of BO (49). As GORD progresses to BO, and BO progresses to OAC, the proportion of HCl and secretions in the refluxate decreases dramatically, leaving predominantly BAs (38,50,51).…”
Section: Bile Acidsmentioning
confidence: 99%
“…In addition, increased urea secretion in the gastrointestinal tract leads to dysbiosis of the intestinal micro ora and disruption of the intestinal epithelial barrier. This leads to reabsorption of ammonia produced by hydrolysis of urea, which accumulates in large quantities in the gastrointestinal tract, via the intestinal mucosa, and resynthesize of urea in the liver, exacerbating renal damage [15].…”
Section: Introductionmentioning
confidence: 99%